Comparison of different analytical methods to evaluate the heat shock protein (HSP) response in fruits. Application to tomatoes subjected to stress treatments - Polenta, Gustavo Alberto; Guidi, Silvina Mabel; Ambrosi, Vanina; Denoya, Gabriela Inés (Elsevier, 2020)
Heat shock proteins (HSP) are synthesized in living tissues exposed to transient increase in temperature and play a central role in the protective response against heat and other stresses. In fruits, this response to heat treatment provides resistance to a physiological alteration known as chilling injury. Despite the physiological importance of this group of proteins, publications comparing different methodological alternatives for their analysis are rather scarce. In the present paper, we conducted a comparative study using different electrophoretic and immunological techniques to evaluate the HSP response in fruits. Proteins were extracted from tomato fruit exposed to an HSP-inducing temperature (38º C) for different times (0, 3, 20, and 27 hours). Different alternatives of analysis (SDS-PAGE, SDS-PAGE followed by IEF, western blot, and dot blot) were performed, and their potential application discussed. The study was complemented with a practical application, in which tomatoes were subjected to heat and anaerobic treatments and then stored in a chill-inducing temperature. This application evidences the relevance of knowing the level of proteins attained by stress treatments which correlates with the acquired tolerance.